VALIDITAS LEMBAR KERJA PESERTA DIDIK (LKPD) ELEKTRONIK PADA MATERI SISTEM KOORDINASI - Peni Defita Sari; Wan Syafi’i; Yustina Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The electronic Student Worksheet (LKPD) is an independent teaching material that utilizes the technology and communication needed by students to study the coordination system material for class XI SMA. The purpose of this study was to produce valid electronic Student Worksheets (LKPD) on class XI SMA coordination system material. This research was conducted at the Biology Education Campus, FKIP, Riau University and SMAN 8 Pekanbaru. This type of research is development research using the ADDIE model, which consists of the Analysis, Design, and Development stages. The data collection instruments used were validation sheets and response questionnaires. Data collection is done by validating the electronic module. The data analysis technique used is quantitative descriptive analysis. The results showed that the validation results of electronic Student Worksheets (LKPD) on the design or appearance aspect obtained an average value of 3.68 with a very valid category, content/material aspects received an average value of 3.87 with a very valid category, Guided-based aspects Discovery gets an average score of 3.92 with a very valid average, and the language feasibility aspect gets an average score of 3.30 with a very valid category. Based on the results of the study, it can be concluded that the electronic Student Worksheet (LKPD) based on Guided Discovery on the coordination system material for class XI SMA that has been developed is included in the very valid category with an average validity value of 3.30, so that the electronic Student Worksheet (LKPD) Based on Guided Discovery that has been developed can be used in Biology learning.Key Words: Electronic LKPD, Guided Discovery, Coordination System